Analysis of Arabic Textbook "Takallam Bil 'Arabiyyah Volume 6" Based on Mickey's Theory - Ritonga, Apri Wardana (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2021)
Textbooks have an important role in achieving learning success. learning will run effectively if the teaching materials used are in accordance with the learning objectives. it is necessary to do an in-depth study of the textbooks used in schools. This study aims to analyze the textbook "Takallam Bil 'Arabiyyah Volume 6" which is used in Arabic learning based on Mackey's theory. This study uses the literature study method. Sources of data were taken from articles, books, research reports, and textbooks "Takallam Bil 'Arabiyyah Volume 6" with data analysis techniques using descriptive analysis. Finally, the data is presented using the deductive method, which describes general phenomena to the findings of the analysis. This research reveals that the textbook "Takallam Bil 'Arabiyyah Volume 6" was compiled based on the theory of William Francis Mackey. This can be seen from the presentation of the material which contains the concepts of selection, gradation, presentation, and repetition. The development of the textbook "Takallam Bil 'Arabiyyah Volume 6" needs to be done by adding more factual material for student life in the 21st-century era.